Trace element distribution and pollution status of surface sediments in lakes impacted by volcanic activity - Apestegui, Aranza; Juncos, Romina; Daga, Romina Betiana; Barriga, Juan Pablo; Rizzo, Andrea Paula; Ribeiro, Sergio (Springer Heidelberg, 2023)
Fil: Apestegui, Aranza. Universidad Nacional de Río Negro; Argentina